‘Repetition without change?’: A critical discourse analysis of selected ZANU-PF advertisements for the July 2013 and July 2018 elections - Albert Chibuwe; Allen Munoriyarwa (SAGE Publications, 2023)
Drawing on Critical Discourse Analysis (CDA), and anchored on CDA theory, we argue that as the ruling party’s governance record increasingly came under scrutiny in two election cycles researched, the Zimbabwe African National Union – Patriotic Front (ZANU-PF), largely maintained its old strategies of power legitimation. However, it altered the message in order to reflect the changing intensity of political contestation, an increasingly bellicose political opposition and growing dissent within its own ranks, as well as the shifting economic fortunes of the country. Forced to campaign under these circumstances, ZANU-PF trusted, with notable variations, its old discourse strategies to produce election advertisements that legitimised its hold on power, hegemony and spread its ideology. The findings show that whereas in July, 2018, the message changed to reflect the leadership change, ZANU-PF’s legitimation strategies remained unchanged. Similarly, we note that whereas the ‘them’ that had to be de-legitimised in 2013 was unequivocally Tsvangirai and the Movement for Democratic Change Tsvangirai (MDC-T), in 2018 ‘them’ not only referred to Nelson Chamisa and MDC Alliance, but it also referred to Mugabe and curiously not ZANU-PF under Mugabe. Including ZANU-PF under Mugabe, we argue, would have also inadvertently de-legitimised both Mnangagwa and ZANU-PF.